HISTORY AND MODERNITY OF “AGENCE FRANCE-PRESSE” - Kacharava, Khatuna (European Scientific Journal, ESJ, 2014)
Agence France-Presse (AFP) is an international French news agency located in Paris. It is the oldest and largest news agency in the world. It is one of four most outstanding agencies together with “Associate Press”, “Reuters” and “Itar-Tass”. Information agencies originated from 1835 when a young French writer and translator Charles-Louis Havas established Agency Havas on the basis of which was established one of the greatest agencies France-Presse. A lot of issues were changed in the strategy of the Agency from the day of its foundation, but in XXI century, the epoch of modern technologies, it faced new challenges and accomplished changes in the sphere of its activities. Top management of Agence France- Presse managed to implement new technologies and become one of the most prestigious agencies in the world.